Legal Certainty of the Proof Power of Notary Deeds in the Concept of Cyber Notary according to Indonesian Positive Law - Iswari, Katrin Yogi; Adzania, Pelangi; Novilawati, Rizka; Samosir, Tetti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The development of technology in the field of notary in the digital era requires notaries to provide public services in accordance with their roles and authorities based on cyber notary. Therefore, the urgency of this study is to analyze the guarantee of legal certainty over the evidentiary power of Notarial Deeds made in the concept of cyber notary along with all the legal consequences that arise, especially for agreements that are required to be in the form of Authentic Deeds. This study is a normative legal research conducted by examining library materials or secondary data which is also commonly referred to as literature study research. This study concludes that there is no legal certainty regarding the evidentiary power of notarial deeds made in the concept of cyber notary according to Indonesian positive law because there are no clear regulations regarding cyber notary based on Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning Notary Positions and Law No. 11 of 2008 concerning Information and Electronic Transactions. There is a degradation of the evidentiary power of notarial deeds which should be authentic deeds that have perfect evidentiary power into private deeds. Such conditions will also ultimately result in the failure to fulfill the formal agreement elements required by legislation and have a further impact on the fulfillment of obligations under legislation that require the use of a notarial deed.